Análisis estático de los elementos de suspensión de un monoplaza tipo formula eléctrico (2019)
Nowadays, it is essential that the suspension elements of the emulation cars have the capacity to withstand a great amount of effort to which they will be submitted and have an optimal per-formance for competitions, being indispensable that the material used meets physical require-ments and / or resistant mechanical properties.  Method: In the first instance, an electric formula type car was designed, being manufactured with university-level engineering studies such as: finite element analysis, redesign and solutions to problems; to give validation of the elements of suspension that can be used in competition, where the evaluation and optimization of the parts of the car are important for its performance, such as the suspension to which a finite element analysis process was carried out in ANSYS used to perfect the vehicle, hoping to give it a stable control by reducing its weight, validating the resistance of the material and the piece designed. It showed a technological breakthrough that proposes advances in engineering studies to feed the ambition of the automotive sector and design engineering, as seen in the big teams of formula 1 in creating suspension elements for their competition vehicles. This example of a single-seater fulfills the objectives of having a rocker as a solid lightweight structure and scissors as a vital element of connection between the frame and chassis, representing benefits to the automotive sector, with the ability of the material to withstand applied loads.